Vulnerabilidade e risco à erosão costeira na Ilha de Mosqueiro/PA e a ocupação humana na orla - SOUSA, Herilene Chaves de (2024)
The beaches are naturally fragile, dynamic, constantly adjusting to natural and anthropogenic conditions. The valorization of the beaches of Mosqueiro Island generates irregular urbanization, added to the natural problems of erosion. Thus, the goal of this work was to classify the edge of Mosqueiro Island in terms of human occupation and analyze the vulnerability and risk to coastal erosion on it. The methodology followed a flowchart, adapted by Lins-de-Barros (2005), which consists of identifying special areas for planning by classifying the degree of vulnerability and risk to coastal erosion, analyzing physical (environmental) and, urban indicators, such as the density and position of buildings. The steps adopted are: the study of physical vulnerability to erosion (1st step), a study of urban indicators (2nd step), assessment of the degree of risk (3rd step), degree of damage (4th step), the study of adaptations and human perception (5th step), definition of special areas for planning (6th step), proposed measures for coastal planning and management (7th step). The results obtained indicated that the physical vulnerability of the beaches has a characteristic of being high, due to the greater occupation of the coastline, destruction of frontal vegetation strips, erosion of the urbanized margin, except for some beaches that presented moderate to weak vulnerability. Regarding the typology of the shoreline, most beaches are in the process of urbanization or present consolidated urbanization, and the landscape is gradually de-characterized. The degree of risk on the edge of the Island is associated with urban occupation, so more urbanized areas present a high risk. The degree of damage on the Mosqueiro Island was mainly absent, as most beaches were recently (in 2019) contemplated with the construction of retaining walls, in such a way that they have minimized much of the tidal action; beaches with mild to moderate damage are affected, albeit moderately, with erosion problems. Except for Marahú and Praia Grande that are still quite affected by hydrodynamics, which made it difficult to finish the retaining walls. The main works present on the Island are infrastructure and protection, such as the walls and passage ducts. The population's perception indicates a positive view in the construction of these structures, being an important parameter for understanding the problems observed. The areas defined for planning are essential so that new residents are not affected. The main mitigating measures to be taken are educational actions in all sectors affected, passive works, and when the previous measures are not effective, structural protection actions must be resorted to.